Efficacy of Novel Carbon Nanoparticle Antioxidant Therapy in a Severe Model of Reversible Middle Cerebral Artery Stroke in Acutely Hyperglycemic Rats - Fabian, Roderic H.; Derry, Paul J.; Rea, Harriett Charmaine; Dalmeida, William V.; Nilewski, Lizanne G.; Sikkema, William K. A.; Mandava, Pitchaiah; Tsai, Ah-Lim; Mendoza, Kimberly; Berka, Vladimir; Tour, James M.; Kent, Thomas A. (Frontiers in Neurology, 2018)
Introduction: While oxidative stress can be measured during transient cerebral ischemia, antioxidant therapies for ischemic stroke have been clinically unsuccessful. Many antioxidants are limited in their range and/or capacity for quenching radicals and can generate toxic intermediates overwhelming depleted endogenous protection. We developed a new antioxidant class, 40 × 2 nm carbon nanoparticles, hydrophilic carbon clusters, conjugated to poly(ethylene glycol) termed PEG-HCCs. These particles are high capacity superoxide dismutase mimics, are effective against hydroxyl radical and functionally recouple nitric oxide synthase. Here we report the effects of PEG-HCCs administered during reperfusion after transient MCA suture occlusion (tMCAO) in the rat under hyperglycemic conditions. Hyperglycemia occurs in 1/3 of stroke patients and worsens clinical outcome. In animal models, this worsening occurs largely by accelerating elaboration of reactive oxygen species during reperfusion. Methods: PEG-HCCs were studied for their protective ability against hydrogen peroxide in b.End3 brain endothelial cell line and E17 primary cortical neuron cultures. In-vivo, hyperglycemia was induced by streptozotocin injection 2 days prior to tMCAO. 58 male Sprague-Dawley rats were analyzed. They were injected IV with PBS or PEG-HCCs (4 mg/kg × 2) at the time of recanalization after either 90 or 120-minute occlusion. Rats were survived for up to 3 days and infarct volume characteristics and neurological functional outcome (modified-Bederson Score) were assessed. Results: PEG-HCCs were protective against hydrogen peroxide in both culture models. In-vivo, improvement was found after PEG-HCCs with 90-minute ischemia with reduction in infarct size (42%), hemisphere swelling (46%), hemorrhage score (53%) and improvement in Bederson score (70%) (p=0.068-0.001). Early high mortality in the 2-hour in the PBS control group precluded detailed analysis, but a trend was found in improvement in all factors, e.g. reduction in infarct volume (48%; p=0.034) and a 56% improvement in Bederson score (p=0.055) with PEG-HCCs. Conclusions: This nano-antioxidant showed some improvement in several outcome measures in a severe model of tMCAO when administered at a clinically relevant time point. Longer term studies and additional models are required to assess potential for clinical use, especially for patients hyperglycemic at the time of their stroke, as these patients have the worst outcomes.